Study on the Distribution of Disease‐Resistant Shrimp Identified by DNA Markers in Respect to WSSV Infection in Different Seasons Along the Entire East Coast of India Aiming to Prevent White Spot Disease in Penaeus monodon. Issue 1 (16th April 2014) - Mallik, A.; Chakrabarty, U.; Dutta, S.; Mondal, D.; Mandal, N.
Summary: White spot disease caused by white spot syndrome virus (WSSV) is responsible for harming shrimp aquaculture industry and results in a pandemic throughout the world. Undeniably, the knowledge on geographic distribution, transmission, virulence, and seasonal prevalence of this disease alongside information on the distribution of disease‐resistant shrimps may be helpful to understand important aspects of disease biology. This study was intended to estimate WSSV prevalence by qualitative and quantitative PCR method among the Penaeus monodon samples collected from four different places namely Digha, West Bengal; Chilika, Orissa; Visakhapatnam, Andhra Pradesh; and Chennai, Tamil Nadu at three different seasons in the period of 2011–2013 from east coast of India. Along with this, the disease‐resistant prevalence was also investigated using earlier developed 71 bp microsatellite and 457 bp RAPD‐SCAR DNA marker among the collected shrimps. Qualitative PCR depicted that the cumulative WSSV prevalence at four places was the lowest (0%) at pre‐monsoon, whereas, it was the highest (21.2%) during post‐monsoon season. Quantitative real‐time PCR showed the average copy number of WSSV to be the highest (~10 3  copy μg −1 shrimp genomic DNA) at post‐monsoon season. Additionally, estimated disease‐resistant prevalence was the highest in Visakhapatnam (79%) and lowest in Digha (21%). It is well known to all that a trait cannot be identified using a single genetic pattern. This study will significantly contribute insight to develop specific pathogen‐resistant (SPR) seeds of P. monodon simultaneously using two DNA markers that would be a cost‐effective and safer approach towards disease prevention instead of conventional trends of seed generation from unselected wild broodstock.